A longitudinal study of ventilation rates in California office buildings and self-reported occupant outcomes including respiratory illness absence. (October 2015) - Mendell, Mark J.; Eliseeva, Ekaterina A.; Spears, Michael; Chan, Wanyu R.; Cohn, Sebastian; Sullivan, Douglas P.; Fisk, William J.
Abstract: Background: Limited evidence has associated lower ventilation rates (VRs) in offices with higher illness-related absence rates. Methods: We studied spaces in office buildings, selected without knowledge of their VRs, in three California climate zones. In each study space, real-time logging sensors measured carbon dioxide and thermal parameters for one year. Web-based surveys every three months collected data on occupants' health outcomes. Using multivariate models, relationships were assessed between CO2 concentrations, or VRs estimated from CO2, and adverse occupant outcomes including respiratory infections and illness absences. For all outcomes, positive associations were hypothesized with higher CO2 levels (and negative associations with higher VRs). Results: Low survey response limited sample size and study power. In the 16 study spaces, CO2 concentrations were uniformly low over the year, and most estimated VRs ranged from twice to nine times the California office minimum VR standard (7 L/s or 15 cfm per person). Primary CO2 and VR metrics had no statistically significant relationships with occupant outcomes. Conclusions: Within the observed range of uniformly low CO2 and high VRs (mostly 16–42 L/s per person), little variation in contaminant concentrations would be expected, which would explain lack of relationships with occupant outcomes. These high VRs resulted partly from frequently used energy-saving "economizer" cycles in moderate California climates, but VRs at other times also substantially exceeded required VRs. These findings suggest, consistent with theory, that within a higher VR range, increased VRs do not reduce respiratory illness. Further studies are needed to better characterize such relationships. Highlights: Ventilation rates (VRs) in California offices and 5 occupant outcomes were studied. Outcomes: respiratory illness, illness absence, symptoms, perceived air quality. VRs in the office buildings studied were very high, from 2 to 9 times the standard. In this high range, primary VR metrics were not associated with occupant outcomes. Within this high range of VRs, increased VRs may not benefit occupants.